Tectono-magmatic significance of the pillow basalts from the ophiolitic mélange of the Dinarides - Šuica, Sanja; Lugović, Boško; Kukoč, Duje (Ofioliti, 2018)
The remnants of the Neotethyis in the area of the Dinarides are represented by numerous ophiolitic complexes and associated mélanges. This paper presents the results of a regional study of pillow basalts and related pelagic sediments. The study area stretches from the northwestern Croatia across the Bosnia and Herzegovina to the southern Serbia. Basaltic rocks are divided into four groups: within-plate alkaline basalts, CAB, E-MORB, IAT and BABB basalts. Pelagic sediments related to basalts with BABB geochemical characteristics yielded Middle Jurassic age. Data presented in this paper as well as previously published data, allowed recognition of two phases of ocean development: (1) the Middle Triassic terminal phase of intracontinental rifting with alkaline basalt, CAB and E-MORB magmatism, (2) compressional phase resulting in IAT and BABB magmatism during Middle and Late Jurassic. These groups are compared to similar rocks in Hellenides. The paper presents the insight into the oceanic evolution of the Neotethys in the Dinaride area - from continental break-up and intiation of sea-floor spreading to compressional stage.